Celebrating Birthdays for Harry Dalva, Peggy Wilson, and Maril Turpin at home of Shirley Griffenhagen and Maril Turpin - Watkins, Howard::::::::: (1978)
Cake Close up: We're Still Here Peggy Harry and Maril. Divorce Roof Collapse and Fire, Liquidation, Depression, Emotional Chaos and Prop 13